2022
DOI: 10.1097/ftd.0000000000000936
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Drug Monitoring of Anti-infective Drugs: Implementation Strategies for 3 Different Scenarios

Abstract: Background: Therapeutic drug monitoring (TDM) supports personalized treatment. For successful implementation, TDM must have a turnaround time suited to the clinical needs of patients and their health care settings. Here, the authors share their views of how a TDM strategy can be tailored to specific settings and patient groups.Methods: The authors selected distinct scenarios for TDM: highrisk, complex, and/or critically ill patient population; outpatients; and settings with limited laboratory resources. In add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…As drug exposure reflects all these underlying factors, TDM may be recommended in patients not responding to treatment when available ( Figure 1 ). 51 54 …”
Section: Standardmentioning
confidence: 99%
See 2 more Smart Citations
“…As drug exposure reflects all these underlying factors, TDM may be recommended in patients not responding to treatment when available ( Figure 1 ). 51 54 …”
Section: Standardmentioning
confidence: 99%
“… 53 , 82 The implementation of TDM can be tailored for specific TB services making use of various types of assays (e.g., high-performance liquid chromatography-ultraviolet, liquid chromatography–mass spectrometry or nanophotometer). 54 , 83 Dose changes guided by TDM should take other clinical parameters into consideration (e.g., severe cavitary disease). 47 High priority populations to consider for TDM include those with HIV co-infection, DM, malnutrition, or children, because these factors increase the probability of pharmacokinetic variability and are independently associated with poor TB treatment outcomes ( Figure 1 ).…”
Section: Standardmentioning
confidence: 99%
See 1 more Smart Citation
“…However, TDM poses many challenges such as uncomfortable sampling methods, requirement for highly trained personnel from the sample collection to analysis, and dry-ice shipping, which all lead to high costs or a lack of availability in TB-endemic settings where poor treatment outcomes are more common and TDM may be of the most benefit [6]. Performing TDM with dried blood spots (DBS), urine, saliva, and hair, in lieu of regular serum or plasma sampling is gaining popularity owing to the relatively simple sample collection and specimens that do not require cold-chain transport [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The TDM approach should be tailored to the specific situation, with a more rapid turnaround time being more important for a population with critical illness than for one with a chronic condition that requires months of or even lifelong therapy. By selecting 3 distinct scenarios for TDM (critically ill patients, outpatients, and remote settings with limited laboratory resources), Kim et al 13 demonstrated that for optimal benefit, TDM strategies must be appropriate for the intended population. For example, the rapid turnaround time for critically ill patients, convenient sampling for outpatients, and feasibility and availability for those in settings with limited laboratory resources proved to be important factors.…”
mentioning
confidence: 99%